Factors affecting adherence to antiretroviral therapy and treatment hub visits of persons living with HIV. - De Torres, Ryan Q.
Adherence to antiretroviral therapy (ART) and treatment hub visits are vital in the control and management of HIV considering the dramatic rise of HIV cases in the Philippines. The study described adherence to ART and treatment hub visit of persons living with HIV (PLHIV) and analyzed the factors affecting it. Association between current adherence to ART and treatment hub visit, and future adherence to ART and treatment hub visit was also examined. -- Third phase of PRECEDE Model explains that there are predisposing, reinforcing, and enabling factors that can affect a behavior. Descriptive correlational study using survey of PLHIV who were in the first six months of ART was implemented. After training, point-of-contact (POC) persons, who had direct contact with the participants, facilitated participants recruitment and data collection through consecutive sampling. Descriptive, correlational and regression analyses were used to analyze quantitative data while summative content analysis was used to analyze qualitative data. -- The final sample, comprising of 225 participants, was found to be homogeneous based on sociodemographic and clinical characteristics. Although there was low adherence to treatment hub visit (47%), adherence to ART (91.2%) was high. The common reasons for sub-adherence were related to time and activity constraints. Multivariate logistic regression did not show association between adherence to ART and treatment hub visit, and with predisposing, reinforcing, and enabling factors. Qualitative analysis showed that barriers and facilitators to ART mostly come at the personal level. Current adherence to ART and treatment hub visit did not show association with future adherence to ART and treatment hub visit in the next 6 and 12 months. Most perceived needed service to promote adherence focused on healthcare which includes free and extended medical services, and accessibility and quality of service. Comprehensive, holistic, and population-based strategies would promote continuing engagement to care among PLHIV.